How functional disability relates to dentition in community‐dwelling older adults in Brazil. (3rd October 2016) - Antunes, JLF; de Andrade, FB; Peres, MA
Abstract : Objective: To assess the association between dentition status and functional disabilities among community‐dwelling older individuals. Subjects and methods: A total of 5012 individuals aged 65–74 were interviewed in 2013 during a nationwide community‐based survey. This cross‐sectional study used a questionnaire including information on dentition, locomotion impairment, difficulties in basic and instrumental activities of daily life, socio‐demographic characteristics, behaviour and general health status. Poisson regression models assessed prevalence ratios (PR) and 95% confidence intervals (95% CI). Results: About 31.3% of older people in Brazil reported having ≥21 preserved teeth, the condition for a functional dentition without prosthetic appliances. This proportion was significantly lower among individuals with locomotion impairment and difficulties in basic and instrumental activities of daily life. After adjusting for relevant covariates, functional dentition remained statistically associated with severe (PR = 0.69, 95% CI = 0.15–0.63) and total (PR = 0.69, 95% CI = 0.26–0.44) locomotion impairments, and difficulties in basic activities of daily life (PR = 0.70, 95% CI = 0.53–0.93). Conclusion: Having a functional dentition was significantly less prevalent among those affected by functional disabilities, and this association is unlikely to be due to insufficient control for relevant covariates. The association between dentition and functional disability is bidirectional and involves a complex interplay of one upon the other, and of factors that influence both outcomes.